Microbiological and epidemiological review of Hantavirus: A Review - Hardi Marif; Kwestan Ali (مجلة الانبار للعلوم البيطرية, 2021)
Hantaviruses are rodent viruses that have a world-wide distribution. Rodents and insectivores act as asymptomatic, chronic, persistently infected carrier hosts, whereas humans are dead end hosts and may exhibit symptoms after an incubation period of between one and six weeks. Hantaviruses infect humans and causing either hemorrhagic fever with renal syndrome (HFRS) or Hantavirus cardiopulmonary syndrome (HCPS). Due to the absence of the treatment and approved vaccine in the USA, European and Asian countries, the public awareness and precautions are the only way of minimizing the risk of Hantavirus infection. This review provides a microbiological and epidemiological summary of the Hantavirus diseases in rodents and human beings. We concluded that the disease is a serious zoonotic disease the affect animals and humans and the mortality rate is really high. A wide range of different diagnostic tests play an important role in the diagnosis of the Hantavirus.